An Environmental Evaluation of Ventilation Systems Aimed at Reducing Indoor Radon Concentration - Licia Felicioni; Martin Jiránek; Barbora Vlasatá; Antonín Lupíšek (Buildings, 2023)
The primary measures against radon in buildings are a tight contact structure or venting the subsoil beneath the building. In many cases, ventilation systems used in buildings to ensure good indoor air quality can also be used to reduce the radon concentration. This study aims to evaluate the environmental impacts of residential ventilation systems for their ability to lower the concentration of this gas. The life cycle assessment methodology was used to assess two kinds of ventilation systems. The results indicate that 95% of environmental impacts are associated with operational emissions, while 5% are associated with embodied ones. Moreover, an increase in radon supply rates resulted in an increase in energy consumption and related emissions, for example, the operational energy of an exhaust ventilation system aimed for a reduction to 200 Bq/m3 in a 9/15 cyclic mode range from 9.69 for a radon supply rate of 50 Bq/m3h to 32.27 for 200 Bq/m3h. These simulations show that ventilation systems cannot be considered universally suitable measures to reduce the radon concentration because they may become very energy demanding, and their environmental impact may be significant even considering the type of energy source. Based on this study, we can determine whether it makes sense for a given radon supply rate and energy source to use a ventilation system to reduce the radon concentration in residential buildings.